Pembuatan Kekasaran Permukaan Material ST 37 terhadap Kecepatan Pemakanan pada Milling Machine - Sugiyanto Sugiyanto; Yogi Prabowo (Proklamasi 45 University, 2018)
One of the ideal geometric characteristics of a component is a smooth or rough surface. In practice, it is not possible to obtain a component with a smooth/rough surface. This is due to several factors, such as the human factor (operator) and the factors of the machines used to make it. However, with technological advancements, the growing apparatus capable of forming surface components with a high degree of fineness/roughness, according to the standard measures applicable in metrology, is advanced by geometric measurement experts through research experience. Fineness level/roughness of a surface is very important role in the planning of a machine component, especially concerning the problem of lubrication friction, wear and tear, resistance to fatigue and so on. Therefore, in the planning and manufacture must be considered first about which machine equipment should be used to make it and how much the cost must be incurred. In order for the process of manufacture, there is no significant deviation, then the characteristics of this surface should be understood by the planner even more by the operator. Communication of surface characteristics is usually done in engineering drawings. But to explain perfectly about the characteristics of a surface seems difficult. The research method is started by preparing instrument that is Milling Machine which is used to make surface roughness and Surface Roughness Tester is done 3 times test with variable speed of food which is different equal to 7,3; 13; 24.5 mm/put. With a speed of 102 rpm Rpm, and a depth of 0.4. Next, determine the material roughness level with Surface Roughness Tester. After all, done will get the data test results, followed by analysis and discussion so that will get final conclusion. From the research results obtained the following results: there is a difference in the level of roughness in each material with different feeding speed. The feed rate of 7.3 mm / put yielded 0.64 μ, 13 mm / put roughness generated 1.32 μ, 24.5 mm / put yielded 3.77 μ. The process of measuring the roughness of the material with the speed of feeding is slower, the smoother the surface roughness, the faster the speed of the feeding the more rough. The range of syrup result is also influenced by the speed of the food. The faster the movement of the range range the wider the surface roughness is the opposite.